Effect of feeding hydroponic barley seedlings to lactating ewes on blood biochemical indexes and growth performance of lambs - Ma, Yan; Guo, Tongjun; Zhang, Zhijun; Amat, Guzalnur; Jing, Yaxing; Tuo, Yong; Hou, Liangzhong (Frontiers in Veterinary Science, 2024)
The aim of this study was to investigate the effects of replacing different ratios of basal diets with hydroponically barley seedlings (HBS) on the serum biochemical indexes and growth performance of lambs. It provides a theoretical basis for the use of HBS in ruminant health and scientific feeding management. In total, 30 ewes were randomly categorised into six groups (two control groups, 4 treatment groups, and 8 replicates in each group). All experiments were conducted under the same feeding and management conditions, on this basis the control group was CK1 and CK2 groups, which CK1 group added 15% corn silage, the treatment groups replacing 5% (group A), 10% (group B), 15% (group C) and 20% (group D) of the basal diet (dry matter basis) with HBS, and the experimental period lasted for 36 days, and the lambs were lactating with their mothers throughout the experimental period. Key results. The contents of total protein(TP) ,albumin(ALB) ,milk fat percentage and total solids (TS) in group C were significantly higher than CK1 and CK2 groups(P<0.05)in milk samples; malondialdehyde (MDA) content in groups A and C was significantly lower than groups CK1 and CK2 (P<0.05), alanine aminotransferase (ALT) and azelaic transaminase (AST) contents in groups A and B were significantly higher than CK1 group (P<0.05), TC content in groups A and D was significantly higher than CK1 and CK2 groups (P<0.05), high-density lipoprotein(HDL-c) content in group D was significantly higher than CK1 and CK2 groups (P<0.01) in blood samples； Body height in C group was significantly higher than CK2 group (P<0.05), ear width in group B was significantly higher than CK1 group (P<0.05). In conclusion, under the conditions of this experiment, HBS instead of 5%-15% of the basal diet could improve the milk quality of lactating Hu ewes and alleviate the oxidative stress of the body.